Knee ligament injuries in wrestlers - Nakajima, K.; Tanaka, T.; Fukuda, N.; Hangai, M.; Ara, Y.; Nishida, Y.; Okuwaki, T. (International Journal of Wrestling Science, 2019)
Objective: To clarify the rate of injuries for each ligament of the knee joint from clinical database of Japanese top wrestlers. Analyzed 938 (654 males and 284 females) clinical records at JISS clinic where all wrestlers. (2009-2013)